(untitled) (Proceedings of the International Conference on Future of Education, 2024)
The use of artificial intelligence is a hot topic in the education field. Embracing chatGPT in higher education has the potential to offer a range of benefits, including increased student engagement, collaboration, and accessibility. However, chatGPT has raised a number of challenges and concerns, particularly in relation to academic honesty and plagiarism. The narrative literature review methodology was used for this conceptual paper on chatGPT which has limited published literature since its launch in November 2022. This paper examines the opportunities and challenges of using chatGPT in higher education, focusing on the potential risks and rewards of this innovation and how universities can address the challenges the tool poses. The paper is underpinned by the Transtheoretical Model which postulates that when people feel fearful, they are motivated to reduce the threat. The paper discusses the main features and capabilities of chatGPT and provides examples of its use in higher education. Furthermore, the paper considers the potential for chatGPT to be used for academic dishonesty and the difficulties of detecting and preventing such abuses. Finally, the paper suggests a range of strategies universities can adopt to ensure that chatGPT is used ethically and responsibly, including developing policies and procedures, providing training and support, and using various methods to detect and prevent cheating